Turn a blind eye - Archer, Jeffrey, 1940- (New York : St. Martin's Press, 2021)
Going undercover to expose corruption in the Metropolitan Police Force, Detective Inspector William Warwick is compromised by a high-profile trial and a teammate's romantic relationship with his suspect.
Keywords: Great Britain. -- Metropolitan Police Office -- Officials and employees -- Fiction; Undercover operations -- Fiction; Police corruption -- Fiction; Detective and mystery fiction